The Influence of Financial Ratio on Profit Growth and Their Implications on Dividend Policy (Empirical Study in Companies Listed on the Indonesia Stock Exchange) - Masno Marjohan (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
This study aims to determine whether financial ratios affect earnings growth and dividend policy. Financial ratios in this study are measured by return on equity, debt-to-equity ratio, total asset turnover, liquidity ratio, and payment policy. Sampling was done using purposeful sampling. Among the 26 companies listed on the Indonesia Stock Exchange (IDX), up to 8 food and beverage companies were used in the sample analysis. The analysis used is multiple linear regression analysis for panel data regression. The three models are general effect, fixed effect, and random effect. After doing the classical normality test, heteroscedasticity test, multicollinearity test, and autocorrelation hypothesis test. Hypothesis testing is done by using the F-test and t-test. The results show that return on equity has a significant effect on profit growth, and the debt/equity ratio has no significant effect on profit growth, which means that return on equity in this study does not necessarily affect profit growth will affect income growth because you are in debt, should pay debts. It is the reason for the high debt/equity ratio, which affects income growth. The total asset turnover rate has no significant effect on profit growth, and the current ratio significantly affects profit growth. Profit growth significantly affects the dividend policy of companies listed on the Indonesia Stock Exchange during 2015 2019. The financial aspect takes into account the availability of dividends and stock prices.